Sistem Diagnosis Penyakit Jantung Menggunakan Metode Modified K-Nearest Neighbor - Kholif Beryl Gibran; Nurul Hidayat; Tibyani Tibyani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Cardia is included in the unit which is very crucial for human physical. As a blood pump to each limb is the main function of the cardia. Loss of the function of the cardia tissue and abnormalities of the cardia regulator and infection can be caused by cardia failure occurs when the cardia is no longer able to meet the level of nutrition and oxygen needs of the body. Based on the report of the World Health Unit (WHO) caused by cardia disease one third of the 58 million people who died in 2005 (Afriansyah 2009). The cause of death number 1 in the world for now is cardia. Cardia disease causes at least 30% of deaths in almost the entire world or about 17 and a half million in 2005. According to the World Health Organization (WHO), while coronary cardia disease itself causes 60% of deaths due to cardia (WHO, 2007). While 26.4 percent of deaths are due to cardiovascular disease including coronary cardia, it is based on the National Census conducted in 2001 (MOH RI, 2003). According to the explanation of the problem that has been described and also according to the exposure of previous studies, therefore the appropriate title for this research is "Diagnosis System for Heart Disease Using the Modified K-NN (MKNN) Method".